An Evaluation on Electronic Patient-Reported Outcomes in Ciparay Sub-District, Bandung, West Java - Kristiani Irawaty, D; Pratomo, H; Djuwita, R; Mediana, A (KnE Life Sciences, 2019)
Electronic Patient-Reported Outcomes for children has become more common as a means to collect health data during conception, pregnancy, and childbirth. However, it remains unclear whether the responsive level of the digital divide on the technology. The purpose of this study was to assess the adoption of an Electronic Patient-Reported Outcomes by mothers to monitor the health status of their infants in Ciparay Sub-District, West Java Province. This study also examined the relationship between demographic characteristics on the utilization of the new technology and perceived barriers for usage. A total of 112 patients had registered into an Electronic Patient-Reported Outcomes entitled ‘Memobayi’ from April to July 2016. Personal and technical factors affected the adoption of electronic technology for recording the health status of their infants. This included lack of knowledge, privacy as well as technical concerns. The result of the study also revealed that although the use of information and communication technologies in Indonesia had overgrown during the last ten years, a considerable gap remained between those with and without access to the adoption of Electronic Patient-Reported Outcomes. Keywords: Electronic Patient-Reported Outcomes, Digital Divide, Memobayi, Ciparay.